A model for testing the relationship between company's size and performance: a cross country analysis. (2018) - Giacosa, Elisa; Ferraris, Alberto; Mazzoleni, Alberto; Vrontis, Demetris
The purpose is to verify whether the company's size (in terms of production value) could be considered as a relevant factor in impacting company performance, taking into consideration the country variable. Italian and German companies have been compared. The country factor (considering its structural and economic characteristics that are different from the company's size) has a primary importance in determining the differences of performance between German and Italian companies. There is a weak relationship between the companies' performance and their size. Size factor is not one of the main factors that explain why the performance of the German companies is better than Italian ones. Global differences are mainly due to the structural and economic characteristics of each country and, in residual form, due to different size of the companies operating in those two countries. The research is characterised by several theoretical and practical implications, especially for top management and investors.